2008
DOI: 10.1017/s0007114507886375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term administration of a cocoa polyphenolic extract (Acticoa powder) on cognitive performances in aged rats

Abstract: Numerous studies have indicated that increased vulnerability to oxidative stress may be the main factor involved in functional declines during normal and pathological ageing, and that antioxidant agents, such as polyphenols, may improve or prevent these deficits. We examined whether 1-year administration of a cocoa polyphenolic extract (Acticoa powder), orally delivered at the dose of 24 mg/kg per d between 15 and 27 months of age, affects the onset of age-related cognitive deficits, urinary free dopamine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 79 publications
0
54
0
Order By: Relevance
“…Another study addressed the effects of long-term (12 months) oral supplementation of the same polyphenolic extract, Acticoa powder, on cognitive functions in aged rats, showing improved cognitive performance in terms of spatial memory and short-and long-term learning. In this light, the authors suggested that Acticoa powder could be beneficial in retarding age-related brain impairments, including cognitive deficits in normal ageing and perhaps neurodegenerative disorders [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another study addressed the effects of long-term (12 months) oral supplementation of the same polyphenolic extract, Acticoa powder, on cognitive functions in aged rats, showing improved cognitive performance in terms of spatial memory and short-and long-term learning. In this light, the authors suggested that Acticoa powder could be beneficial in retarding age-related brain impairments, including cognitive deficits in normal ageing and perhaps neurodegenerative disorders [28].…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47] A recent clinical study has demonstrated an acute increase of brain perfusion following ingestion of flavanol-rich cocoa. 48,49 Moreover, long-term administration of cocoa flavanols to aging rats is associated with preservation of youthful cognitive performance 50 -raising the possibility that cerebral hypoxia (and/or suboptimal cerebrovascular nitric oxide production) might also play a role in the more modest fall-off in cognitive function associated with healthy aging. These considerations suggest that regular consumption of cocoa flavanols might have important potential for promoting retention of cognitive function as humans age.…”
mentioning
confidence: 99%
“…In fact, acetylcholine is a regulatory cofactor for many processes associated with the development of the brain and nervous system, and choline containing during an embryo's development adjusts the 4 Avicenna J Neuro Psych Physio. 2016; 3(1):e34444.…”
Section: Discussionmentioning
confidence: 99%
“…A diet full of antioxidants improves brain damage and enhances cognitive function (4), and recent studies have demonstrated that ginger produces both antioxidant activity and neuron-protection activity (5,6).…”
Section: Introductionmentioning
confidence: 99%